THE INFLUENCE OF ACTIVITIES AND SOLVENCY ON THE PROFITABILITY OF FOOD AND BEVERAGE COMPANIES LISTED ON THE IDX - Andrinaldo, Arisky; Nurhayati, Yuli; Famalika, Ade; Yeni, Revita Andri (Dynamic Management Journal, 2024)
The purpose of this study was to determine the impact of activity levels and solvency on food and beverage companies listed on the Indonesian Stock Exchange. The study is a quantitative study using secondary data in the form of financial reports of his 2018-2021 food and beverage companies listed on the Indonesian Stock Exchange in April 2021. A targeted sampling technique was used to determine the sample for this study. Classical hypothesis testing and multiple linear analysis were used for data analysis. The independent variables used in this study are activity (X1) and ability to pay (X2) and the dependent variable profit (Y). The findings of the study show that while activity level does not have a significant impact on the profitability of food and beverage companies listed on the Indonesian Stock Exchange, solvency levels can have a significant impact on profitability. indicates that On the one hand, the relationship between activity and solvency (collectively) affects the profitability of companies listed on the Indonesian Stock Exchange.